Degenerasi nilai-nilai pancasila pada sekolah dasar: tantangan dan strategi implementasi pendidikan di era globalisasi. - Salma Endrylia; Nuri Nurlita; Yogi Adi Nugraha Mulyawan; Auliya Aenul Hayati (Jurnal Pendidikan Dasar, 2026)
Abstract Classroom Action Research (CAR). Using the Kemmis Spiral and MC Taggart models, there are four stages: planning, implementation, observation, and reflection. The goal was to foster curiosity through Problem-Based Learning (PBL) methods integrated with open-ended questions via a Google Form questionnaire. The study was conducted among 35 sixth-grade students at SDN Bima Cirebon.Students' mastery of Pancasila values averaged 87%, categorized as very strong. This indicates that most students understood the Pancasila material taught and related it to concrete situations in their daily lives. The dimension of mutual respect and upholding unity averaged 88%, reflecting students' habit of appreciating differences in perspective, background, and the diversity of their peers at school. This indicates that the principles of tolerance and the spirit of unity have been internalized and are visible in the patterns of social relations between school resident.The indicators of caring and mutual cooperation also reached an average of 88%, as evidenced by students willingness to help their peers, collaborate on group assignments .The average percentage of 90% with very strong criteria means that it shows that the majority of students in the school environment do not experience in the questionnaire for testing understanding of discipline and politeness.